Future vision for the quality assurance of oncology clinical trials - FitzGerald, MD, Thomas; Bishop-Jodoin, BS, Maryann; Bosch, DSc, Walter; Curran, MD, Walter J.; Followill, PhD, David; Galvin, DSc, James M.; Hanusik, AB, Richard; King, MS, Steven R.; Knopp, MD, PhD, Michael V.; Laurie, BS, Fran; O'Meara, BS, RT(R)(T), Elizabeth; Michalski, MD, MBA, Jeff M.; et al. (Frontiers in Oncology, 2013)
The National Cancer Institute clinical cooperative groups have been instrumental over the past 50 years in developing clinical trials and evidence based process improvements for clinical oncology patient care. The cooperative groups are undergoing a transformation process as we further integrate molecular biology into personalized patient care and move to incorporate international partners in clinical trials. To support this vision, data acquisition and data management informatics tools must become both nimble and robust to support transformational research at an enterprise level. Information, including imaging, pathology, molecular biology, radiation oncology, surgery, systemic therapy and patient outcome data needs to be integrated into the clinical trial charter using adaptive clinical trial mechanisms for design of the trial. This information needs to be made available to investigators using digital processes for real time data analysis. Future clinical trials will need to be designed and completed in a timely manner facilitated by nimble informatics processes for data management. This paper discusses both past experience and future vision for clinical trials as we move to develop data management and quality assurance processes to meet the needs of the modern trial.